2020
DOI: 10.1136/bmj.m3582
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hospital admission with coronavirus disease 2019 in healthcare workers and their households: nationwide linkage cohort study

Abstract: ObjectiveTo assess the risk of hospital admission for coronavirus disease 2019 (covid-19) among patient facing and non-patient facing healthcare workers and their household members.DesignNationwide linkage cohort study.SettingScotland, UK, 1 March to 6 June 2020.ParticipantsHealthcare workers aged 18-65 years, their households, and other members of the general population.Main outcome measureAdmission to hospital with covid-19.ResultsThe cohort comprised 158 445 healthcare workers, most of them (90 733; 57.3%) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
282
2
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(322 citation statements)
references
References 23 publications
17
282
2
9
Order By: Relevance
“…[4][5][6] Amongst these 'highrisk' groups are healthcare workers (HCWs) 6,7 in whom an increased risk of hospitalisation with COVID-19 has also been demonstrated. 8 Within a HCW population, it has been shown that risk of SARS-CoV-2 infection, differs by occupational role and is highest in 'front-door' and patient facing specialities, 8,9 implying that at least some of the increased risk faced by HCWs is mediated through occupational exposure to SARS-CoV-2. In recognition of this risk the UK Joint Committee on Vaccination and Immunisation (JCVI) listed frontline HCWs as a priority group for receiving vaccination against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Amongst these 'highrisk' groups are healthcare workers (HCWs) 6,7 in whom an increased risk of hospitalisation with COVID-19 has also been demonstrated. 8 Within a HCW population, it has been shown that risk of SARS-CoV-2 infection, differs by occupational role and is highest in 'front-door' and patient facing specialities, 8,9 implying that at least some of the increased risk faced by HCWs is mediated through occupational exposure to SARS-CoV-2. In recognition of this risk the UK Joint Committee on Vaccination and Immunisation (JCVI) listed frontline HCWs as a priority group for receiving vaccination against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the coronavirus 2019 (covid-19) pandemic, healthcare workers have shown a remarkable resilience and professional dedication despite a fear of becoming infected and infecting others 1. In a linked paper (doi:10.1136/bmj.m3582), Shah and colleagues now report robust and concerning findings regarding the risks of covid-19 among health workers and their households 2…”
mentioning
confidence: 99%
“…According to our one-stage reconstructive approach, we have achieved excellent morpho-aesthetic and functional outcomes, comparable with microsurgical reconstructive techniques in agreement with the most recent literature [6] , [9] . Moreover, we have drastically reduced the necessity of tracheostomy, decreased anaesthesia and operative time, diminished hospital and ICU stay with an increased safety because of the emerging evidence of a higher mortality with a 23.8% rate in case of perioperative COVID-19 contagion [11] . Furthermore, if compared to our experience in HNmicrosurgical reconstruction, our management allowed a faster patient turn over, with the possibility of treating an increased number of oncological patient despite the limitations of the period.…”
Section: In This Current Global Lockdown Scenario Cancer Screening Omentioning
confidence: 99%